Economic evaluation of eribulin as second-line treatment for metastatic breast cancer in South Korea - Tremblay G; Majethia U; Breeze JL; Kontoudis I; Park J (Dove Medical Press, 2016)
Gabriel Tremblay,1 Unnati Majethia,2 Janis L Breeze,3 Ilias Kontoudis,4 Jeongae Park5 1Geneconomics Inc., Lévis, Quebec, Canada; 2Global Value and Access, Eisai Inc., Woodcliff Lake, NJ, 3Tufts Clinical and Translational Science Institute, Tufts University, and Institute for Clinical Research and Health Policy Studies, Tufts Medical Center, Boston, MA, USA; 4Global Value and Access, Eisai Limited, Hatfield, Hertfordshire, UK; 5Eisai Korea Inc., Gangnam-gu, Seoul, South Korea Background: Metastatic breast cancer (MBC) is associated with poor prognosis, particularly for those patients with human epidermal growth factor receptor (HER2)-negative tumor. Similar to the rest of the world, treatment options are limited in South Korea following first-line chemotherapy with anthracyclines and/or taxanes. This study examined the cost-effectiveness and cost-utility of eribulin in South Korean patients with HER2-negative MBC who have progressed after usage of at least one chemotherapeutic regimen for advanced disease (second-line therapy).Methods: A partition survival model was developed from the perspective of the South Korean health care system. The economic impact of introducing eribulin as second-line therapy for HER2-negative MBC was compared to that of capecitabine and vinorelbine. The analysis estimated incremental cost per life-year (LY), that is, cost-effectiveness, and cost per quality-adjusted life-year (QALY), that is, cost-utility, of eribulin for management of HER2-negative MBC in South Korea. The model accounted for overall survival, progression-free survival, drug costs, grade 3/4 adverse events, and health care utilization. Deterministic and probabilistic sensitivity analyses were performed to identify uncertainty in the results of the economic evaluation.Results: Second-line eribulin was associated with greater benefits in terms of LY and QALY, compared to capecitabine and vinorelbine. The incremental cost-effectiveness ratio was ₩10.5M (approximately USD 9,200) per LY, and the incremental cost-utility ratio was ₩17M (approximately USD 14,800) per QALY in the basecase analysis. The incremental cost-utility ratio ranged from ₩12M (USD 10,461) to ₩27M (USD 23,538) per QALY in the deterministic sensitivity analysis. In the probabilistic sensitivity analysis, >99% of the simulations were below ₩50M (USD 42,300), and the lower and upper 95% confidence intervals were ₩3M (USD 2,600) and ₩24M (USD 20,900) per QALY, respectively.Conclusion: There currently exist a limited number of treatment choices for women with HER2-negative MBC. Eribulin is a cost-effective option for second-line therapy in South Korea and should be added to the current indications for reimbursement. Keywords: eribulin, metastatic breast cancer, cost-utility, economic analysis